SCIENTIFIC ANALYSIS OF RESEARCH ON IMAM AT-TERMIZI (Scientific journal of the Fergana State University, 2025)
Imam at-Tirmidhi is one of the most famous hadith scholars and scholars of the Islamic world, and his scientific legacy includes important aspects of hadith science, ethics, Sufism, and scientific methodology. This study analyzes the philosophical views developed by Imam at-Tirmidhi. The study examines his scientific methodology in examining hadiths, his approaches to mysticism and spiritual perfection, moral virtues, and the promotion of moral values in society. Imam at-Tirmidhi, combining science and reason, attached great importance to the spiritual development of man and the formation of moral character. His legacy must be studied and applied in practice even today, both scientifically, religiously, and socially.